Extreme Rainfall Trends and Hydrometeorological Disasters in Tropical Regions: Implications for Climate Resilience - Yanfatriani, Elsa; Marzuki, Marzuki; Vonnisa, Mutya; Razi, Pakhrur; Hapsoro, Cahyo A.; Ramadhan, Ravidho; Yusnaini, Helmi (Emerging Science Journal, 2024)
Hydrometeorological disasters due to extreme weather events represent a significant threat to the security of life in Jambi Province. In order to develop effective strategies for mitigating this threat, it is essential to gain a comprehensive understanding of the underlying dynamics that give rise to such disasters. Despite the high frequency of these events, more research is needed on the complex relationship between trends in extreme indices and the frequency of hydrometeorological disasters in this region. This study addresses this gap by utilizing rainfall data from 2008 to 2020 from the Integrated Multi-satellite Retrievals for GPM (IMERG) and hydrometeorological disaster data from the National Disaster Management Agency (BNPB). A range of extreme rainfall indices, including PRCPTOT, R85P, R95P, R99P, CWD, CDD, R1mm, R10mm, R20mm, R50mm, RX1Day, RX5Day, and SDII, were subjected to careful analysis concerning hydrometeorological disasters, including floods, landslides, tornadoes, droughts, and forest fires. Notable results indicate a significant increasing trend (p < 0.05) for the CWD index, while decreasing trends are observed for R85P, R95P, R99P, R50mm, RX1Day, RX5Day, and SDII. PRCPTOT and R20mm show decreasing trends, and CDD shows an increasing trend, although it is not statistically significant (p > 0.05). Subsequently, there was a significant increase in landslides and tornadoes, while forest fires and floods showed an insignificant increase (p > 0.05). Drought exhibited a significant decreasing trend in Jambi. Correlation analysis revealed the complex relationship between extreme weather indices and hydrometeorological disasters. The positive correlations observed between most extreme rainfall indices and floods and landslides, except for CDD, indicate that extreme rainfall is the primary cause of these disasters in Jambi. The correlation is particularly pronounced in areas with mountainous topography, where landslides are more prevalent. The positive correlations observed between CDD and droughts and forest fires suggest that periods of reduced rainfall and increased drought contribute to these disasters. This correlation is more robust in districts with extensive peatlands. The results provide valuable insights into the vulnerability of Jambi Province to hydrometeorological disasters and highlight the importance of understanding regional variations in extreme weather events. These findings improve our understanding of the interactions between climate indices and disasters and provide the basis for informed risk reduction and adaptation strategies in changing climatic conditions. Doi: 10.28991/ESJ-2024-08-05-012 Full Text: PDF